2008
DOI: 10.1159/000113047
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Endometrial Cancer in Women on Tamoxifen: The Role of Liquid-Based Endometrial Cytology – Cytohistological Correlation in a Population of 168 Women

Abstract: Aims: The aim of this study was to evaluate the utility of liquid-based cytology for endometrial surveillance in patients receiving tamoxifen. Methods: One hundred and sixty-eight women scheduled for hysteroscopy were enrolled in the study. The women sequentially underwent hysteroscopy, endometrial cytology and biopsy. Results: Endometrial biopsy only was inadequate in 112 (67%) patients, both endometrial biopsy and cytology were inadequate in 19 (11%) patients, endometrial cytology only was inadequate in 4 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…37 Many studies have evaluated the surveillance of women undergoing long-term tamoxifen treatment, but the best method remains to be determined. 38 Buccoliero et al, 33 in a series of 33 patients receiving tamoxifen, observed a 100% correlation between the endometrial LBC and biopsy results.…”
Section: Published Data On Endometrial Lbcmentioning
confidence: 93%
See 4 more Smart Citations
“…37 Many studies have evaluated the surveillance of women undergoing long-term tamoxifen treatment, but the best method remains to be determined. 38 Buccoliero et al, 33 in a series of 33 patients receiving tamoxifen, observed a 100% correlation between the endometrial LBC and biopsy results.…”
Section: Published Data On Endometrial Lbcmentioning
confidence: 93%
“…The overall sensitivity and specificity of cytology were 95% and 66% when EC and atypical cytology specimens were considered to be positive. Overall, cumulative data in the literature on nearly 4000 patients revealed a sensitivity ranging from 78% to 100% and specificity from 95% to 100%, with a PPV of 78–100% and NPV of 96–100% …”
Section: Published Data On Endometrial Lbcmentioning
confidence: 99%
See 3 more Smart Citations